Developing Modules of Spiritual Body Oriented Psychotherapy (S-BOP) To Enhance Human Potential - Norizan, Yusof; Muhammad Nubli, Abdul Wahab (Universiti Malaysia Pahang, 2017)
This paper describes the process of developing a systematic module that will be used by the student group in the technical training institute. This module of Body Oriented Psychotherapy (BOP) framework integrates with new element which is the spiritual element. In general, the module process in this study uses the ADDIE method (Analyse, Development, Design, Implement and Evaluate). Development of the module through analysing the prerequisite for the module development is subsequently followed by designing, developing and implementing modules. Each stage necessitates an assessment in ensuring the compatibility of the developed module with the target group for module development. Among the instruments adopted in the module development study included module prototypes, media and module reliability questionnaires which was customized to meet objective of the study. The module development method is described with clarity in this paper. Result from this study explains the importance of developing a BOP module that is integrated with spiritual elements for the development of potential and identity. In fact, the importance of spiritual elements can enhance the development of a student's identity in the Technical Training Institute.The spiritual integrity in BOP is a value-added element and improves the quality of counselling and psychotherapy sessions conducted at the Technical Institute.